Mobility of Synaptic Vesicles in Nerve Endings Monitored by Recovery from Photobleaching of Synaptic Vesicle-Associated Fluorescence - Kraszewski, Kajetan (J Neurosci, 1996)
In nerve terminals, synaptic vesicles form large clusters anchored to the presynaptic plasmalemma. Recently, FM1-43 photobleaching experiments carried out at frog motor endplates demonstrated lack of lateral intermixing of synaptic vesicles within clusters, even during sustained nerve terminal stimulation (Henkel and Betz, 1995; Henkel et al., 1996b). We now have investigated the mobility of synaptic vesicle membranes during the endocytic limb of their exo-endocytic cycle. To this aim, we have carried out photobleaching experiments on nerve terminals of hippocampal neurons prelabeled with CY3-conjugated antibodies directed against lumenal epitopes of synaptotagmin I. This conjugate is taken up specifically by synaptic vesicle membranes during endocytosis and then is recovered in newly formed synaptic vesicles. Using this method, we show that synaptic vesicle membranes intermix after endocytosis. Staurosporine, which at hippocampal synapses partially inhibits unloading of FM1-43, but does not block uptake of antibody probes, prevents this intermixing. Our results indicate that synaptic vesicle docking and/or fusion with the plasmalemma correlate with the release of their membranes from a restraining matrix that hinders their lateral mobility. They suggest that membrane intermediates involved in synaptic vesicle reformation interact with a distinct, highly dynamic cytoskeleton and that newly formed synaptic vesicles are recaptured at random within vesicle clusters. Staurosporine, by inhibiting mobility within the terminal, may favor recapture of new vesicles near sites of endocytosis.